2020
DOI: 10.3390/biology9110370
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factors (CGF) Induce Osteogenic Differentiation in Human Bone Marrow Stem Cells

Abstract: Bone regeneration is a complex process regulated by several factors that control overlapping biological processes, coordinating interactions among distinct cell populations. There is a great interest in identifying new strategies for inducing osteogenesis in a safe and efficient manner. Concentrated Growth Factor (CGF) is an autologous blood derived product obtained by centrifugation of venous blood following the procedure set on the Silfradent device. In this study the effects of CGF on osteogenic differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…Venous blood (8 mL) from 5 healthy, non-smoking adult donors, two females and three males, aged between 27 and 50 years old, was collected and immediately centrifuged by a Medifuge device (Medifuge MF200; Silfradent srl, Forlì, Italy), at 25 °C, using a program with the following characteristics: 30 s acceleration, 2 min 2700 rpm, 4 min 2400 rpm, 4 min 2700 rpm, 3 min 3000 rpm, and 36 s deceleration and stop, to obtain CGF clot, as previously described [ 36 , 38 ]. Informed consent was obtained from the donors included in this study in accordance with Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous blood (8 mL) from 5 healthy, non-smoking adult donors, two females and three males, aged between 27 and 50 years old, was collected and immediately centrifuged by a Medifuge device (Medifuge MF200; Silfradent srl, Forlì, Italy), at 25 °C, using a program with the following characteristics: 30 s acceleration, 2 min 2700 rpm, 4 min 2400 rpm, 4 min 2700 rpm, 3 min 3000 rpm, and 36 s deceleration and stop, to obtain CGF clot, as previously described [ 36 , 38 ]. Informed consent was obtained from the donors included in this study in accordance with Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the effects of CGFs on tissue regeneration of alveolar and sinus bone, fracture repair, and implant stability, displaying a good tissue regenerative property [ 29 , 33 , 34 , 35 ]. Some research also showed the effects of CGFs on the osteogenic differentiation of rabbit periosteum-derived cells and human bone marrow stem cells in vitro [ 36 , 37 ], and reported CD34 positive stem cells in CGFs [ 24 , 37 ]. However, to the best of our knowledge, the CGF effects on the neo-vascularization process have not yet been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“… Yu and Wang (2014) [ 40 ] Beagle-PDLSCs Proliferation, osteogenic differentiation Cell counting and an MTT assay; Mineralization nodule counts, ALP activity, western blotting, qPCR (BSP, OCN, COL1a1), and immunohistochemistry CGF promoted PDLSCs proliferation and osteogenic differentiation in a time- and dose-dependent manner. Rochira et al (2020) [ 41 ] h-BMSCs Osteogenic differentiation ALP activity, ARS, western blotting, qPCR (RUNX2, OSX, OPN, COL1a1) CGF alone can induce osteogenic differentiation in h-BMSCs. High RUNX2 expression and RUNX2 nuclear translocation are molecular mechanisms of h-BMSCs osteogenic differentiation induced by CGF.…”
Section: Effects Of Cgf On Scs In Dpc Regenerationmentioning
confidence: 99%
“…However, some studies have reported a lack of dose dependence, which may be attributable to the different methods used to prepare CGF [ 34 , 38 ]. Three methods for preparing CGF have been described to date—namely, spontaneous release into a medium [ 41 ], freeze-drying [ 47 ], and freeze-thawing [ 16 ]. The first two methods are often used in in vitro studies of CGF and yield highly variable extract variable concentrations.…”
Section: Effects Of Cgf On Scs In Dpc Regenerationmentioning
confidence: 99%
See 1 more Smart Citation